Productivity Optimization In A Diverse Working Environment: The Case Of Pec-My Sdn Bhd - Palaninathan, Pa Vikneswaran; Sahayan, Anthony; ., Ananthakumar (2014)
This paper’s main objective is to identify the main problems that caused PEC-MY not being able to meet their challenge goals in terms of productivity and failure cost management. Secondly, this project also takes a look into the possible solutions that can be implemented to overcome these problems in three different strategic phases which is deemed suitable and matching to the organizations cost competitiveness and cost advantageous business strategy. This thesis starts by describing briefly on the industry and its advantages and later moves on to the issues encountered by the company towards achieving productivity optimization and meeting the organizations target and challenge goals.